Haemoconcentration risk at the end of pregnancy: effects on neonatal behaviour. Issue 8 (6th February 2017) - Aranda, Nuria; Hernández-Martínez, Carmen; Arija, Victoria; Ribot, Blanca; Canals, Josefa
Abstract: Objective: To determine the associations between haemoconcentration at the end of pregnancy (third trimester and delivery) and neonatal behaviour in healthy pregnant women supplemented with moderate doses of Fe. Design: A prospective longitudinal study in which obstetric and clinical history, maternal toxic habits, maternal anxiety and Hb levels were recorded at the third trimester and delivery. Neonatal behaviour was assessed at 48–72 h of age using the Neonatal Behavioral Assessment Scale. Setting: Unit of Obstetrics and Gynaecology of the Sant Joan University Hospital in Reus, Tarragona (Spain). Subjects: A total of 210 healthy and well-nourished pregnant women and their full-term, normal-weight newborns. Results: The results showed that, after adjusting for confounders, in the third trimester the risk of haemoconcentration (6·2 % of pregnant women) was related to decreased neonatal state regulation ( B =−1·273, P =0·006) and alertness ( B =−1·848, P =0·006) scores. In addition, the risk of haemoconcentration at delivery (12·0 % of pregnant women) was also related to decreased neonatal state regulation ( B =−0·796, P =0·021) and poor robustness and endurance ( B =−0·921, P =0·005) scores. Conclusions: Our results show that the risk of haemoconcentration at the end of pregnancy is related to the neonate's neurodevelopment (and self-regulation capabilities), suggesting that Fe supplementation patterns and maternal Fe status during pregnancy are important factors for neurodevelopment which may be carefully controlled.